2021
DOI: 10.11114/ijsss.v9i5.5286
|View full text |Cite
|
Sign up to set email alerts
|

Foundational Leadership Theory: A New Ethical Approach to Reducing Knowledge-Hiding Practices Among Employees

Abstract: Knowledge hiding is a destructive behavior that degrades organizational success. Knowledge hiding is the intentional withholding of information from another employee. It has been reported that 76% of U.S. employees hide knowledge from each other. The displaced aggression theory suggests that employees are more likely to hide knowledge from others in the presence of mistreatment by a leader. Therefore, there was a need to investigate new ethical theories that have been shown to influence organizational commitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Ethical leadership improves LMX relationships (Gallie et al, 2017), and UMT confirms that opposing beliefs degrade positive behaviors and attitudes (Yang & Wei, 2017). However, foundational leadership integrity, assurance, and pragmatism reduce counterproductive behaviors (Fuller, 2021a) but improve LMX relationships (Fuller, 2021b).…”
Section: Organizational Citizenship Behavior and Ethical Leadershipmentioning
confidence: 89%
See 4 more Smart Citations
“…Ethical leadership improves LMX relationships (Gallie et al, 2017), and UMT confirms that opposing beliefs degrade positive behaviors and attitudes (Yang & Wei, 2017). However, foundational leadership integrity, assurance, and pragmatism reduce counterproductive behaviors (Fuller, 2021a) but improve LMX relationships (Fuller, 2021b).…”
Section: Organizational Citizenship Behavior and Ethical Leadershipmentioning
confidence: 89%
“…Each measurement consists of a seven-point Likert-typed scale (1 = strongly disagree, 7 = strongly agree) with a previous Cronbach's alpha of .95 (Fuller, 2022b). Previous research has shown that LEAD has a significant relationship with organizational commitment (Fuller, 2021c) and reduces knowledge hiding between employees (Fuller, 2021a). Because pragmatism reduces destructive behaviors, PDT should not moderate the FLP relationship with OCB.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations